An augmented food strategy leads to complete energy compensation during a 15‐day military training expedition in the cold. Issue 11 (31st May 2021) - Charlot, Keyne; Chapelot, Didier; Siracusa, Julien; Lavoué, Chloé; Colin, Philippe; Oustric, Pauline; Thivel, David; Finlayson, Graham; Bourrilhon, Cyprien
Abstract: Soldiers on military expeditions usually fail to compensate for the increase in energy expenditure, with potential deleterious consequences. We therefore analyzed the characteristics of energy compensation in 12 male soldiers, during a 15‐day expedition in the cold, while alleviating some of the contextual limitations of food intake (~20‐MJ daily bags of easy‐to‐use, highly palatable and familiar foods with multiple and long breaks allowed during the day). Body and fat mass losses were low and moderate, respectively (−1.13 ± 1.42% and −19.5 ± 15.6%, respectively, p <  .021). Mean energy intake (EI) was high (~16.3 MJ) and increased at each third of the expedition (15.3 ± 2.1, 16.1 ± 2.1, and 17.6 ± 2.0 for D1–5, D6–10 and D11–15, respectively, p <  .012). This resulted in reaching a neutral energy balance as soon as the D6 to 10 period and reaching normal energy availability during D11 to 15. Participants only increased their EI during the mid‐day (10:00–14:00) period ( p =  .002) whereas hunger and thirst only increased in the morning, with higher scores during D11–15 than D1–5 ( p <  .009). Last, the reward value of sweet foods was also higher during D11–15 than during D1–5 ( p =  .026). The changes in body mass were positively associated with EI ( r =  0.598, p =  .040) and carbohydrate intake ( r =  0.622, p =  .031). This study indicates that complete energy compensation can be reached in challenging field conditions when food intake is facilitated, offering some guidelines to limit energy deficit during operational missions. Abstract : We analyzed the characteristics of energy compensation in 12 male soldiers, during a 15‐day expedition in the cold, while alleviating some of the contextual limitations of food intake (~20‐MJ daily bags of easy‐to‐use, highly palatable and familiar foods with multiple and long breaks allowed during the day). This study indicates that complete energy compensation can be reached in challenging field conditions when food intake is facilitated, offering some guidelines to limit energy deficit during operational missions.